Evaluation of Antimalarial Activity of Sesquiterpene Lactones of Wild Sudanese Basil (Ocimum basilicum L.) through their in vitro Inhibition of Dihydrofolate Reductase (DHFR) - Elhussein, Salah Ahmed; Mabubu, Juma Ibrahim; Osman, Nour Ahmed; Hua, Hongxia (IISTE, 2015)
Sudan is one of the countries severely afflicted with malaria. The spread of resistance of the malaria parasite Plasmodium falciparum to currently used antimalarial drugs calls for continued efforts to discover new ones. Basil (Ocimum basilicum L), which grows widely as a rainy season wild annual plant, is used, limitedly though, as one of the folk remedies of malaria in Sudan. In this study, crude ethanol extracts of the leaves of wild basil caused 100%, 79.8% and 49% inhibition of the growth of P. falciparum, at doses of 500, 50 and 5 µg/ml, respectively, when tested in vitro using RPMI 1640 media. Subsequent work focused on Sesquiterpene lactones present in the ethanol extract of basil, isolated as a group by the method of Harborne (1989) and further separated by preparative TLC, yielding 11 individual compounds. These separated compounds were evaluated for potential antimalarial activity by assaying their in vitro inhibition of dihydrofolate reductase (inhibitors of this enzyme deprive protozoa, as well as bacteria, of reduced folates, carriers of one-carbon fragments required for the biosynthesis of nucleic acids). Inhibition of DHFR was carried out using a commercially available DHFR enzyme (Sigma Co., USA) and spectrophotometrically following the coupled conversion of NADPH to NADP+. Of the eleven compounds, eluted from TLC plates and tested, two were inhibitory to DHFR, resulting in specific activities of 17.2 and 8.7 µmole/min/mg protein. Further work is underway.